EARLY VEGETATIVE GROWTH OF BARLEY AND TRITICALE SOWN AT DIFFERENT SEED AND DAP FERTILIZER RATES UNDER RAINFED CONDITIONS - ABBAS , DILSOUZ NOORI; OMER, FATHI A. (Journal of Duhok University, 2022)
This study was carried out during the growing season 2020-2021 at two locations (Sumail and Zakho) to study the influence of different seeding (2,500000, and 3000,000 and 3,500000 seeds.ha-1) and DAP (0, 200, and 300 kg.ha-1) rates on some early growth characters of barley (Hordeum distichum L.) and Triticale (X Triticosecale wittmack). The experimental was designed as factorial of three factors in a randomized complete block design (RCBD) with three replications. Some early and pre harvest (flag leaf area, plant height, number of total tillers and number on fertile tillers) were measured. The results displayed significant superiority of all studied characters for Zakho location compered to Sumail location. Also, Barley surpassed Triticale crop in flag leaf area, plant height, but inferior in number of total and fertile tillers. Higher numbers of tillers were recorded in Sumail location of experiment with lower seeding rate (314.17 tillers) compared to Triticale or other seeding rate or Fertilizer treatments. DAP fertilizer treatment enhanced most of the studied traits while their effect was not reached significant level. The results recommend that the crops or varieties with fewer tillers are favorable in water limited environments and more studies are recommended mainly for Triticale crop as the studies on this crop in our areas are very rare rather than its economic importance in feeding and food processing